Health and Wellbeing of India's Young People Challenges and Prospects - Bharat, Shalini; Sethi, Geeta; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume fills a major gap in the evidence base on adolescents and youth in India by bringing together research, policy critiques and programme analyses in an intersectoral and multidisciplinary way. With about 373 million persons between the ages of 10 and 24 years, India has the largest number of young people of any country in the world. While this large cohort presents an excellent opportunity to reap a rich demographic dividend, their potential can be realised only with intelligent investments, which create well nourished, healthy, appropriately educated and skilled youth. This volume is based on desk reviews and is complemented by discussions with experts in 4 key thematic areas: nutrition, sexual and reproductive health, mental health and livelihoods, overall focusing on the health and wellbeing of the young in India. Each chapter provides a comprehensive picture of the current situation in a focal theme and identifies significant gaps in information/data and programmes. In addition, it explores the scenario of building capacity for undertaking research on, and with adolescents, through a qualitative needs assessment. This timely volume provides a thorough overview of related research, policy and programmes for a wide group of social and behavioural scientists and public health experts interested in India's young people. .
Chapter 1. Adolescents and Youth: Setting the Context Geeta Sethi and Shalini Bharat -- Chapter 2.Adolescent and Youth Nutrition in India Hemal Shroff and Deepa Shokeen -- Chapter 3. Adolescent and Youth Mental Health in India: Status and Needs Chetna Duggal and Lamia Bagasrawala -- Chapter 4. Adolescent and Youth Mental Health in India: Policies and Programs Chetna Duggal and Lamia Bagasrawala -- Chapter 5. What Do We Know About Sexual and Reproductive Health of Adolescents and Youth in India?: A Synthesis of Literature M. Sivakami and Saurabh Rai -- Chapter 6. Mapping Social Innovation among Youth and Adolescents: A Situational Assessment of Livelihood Promotion and Enhancement Initiatives in India Sunil D. Santha, Swati Banerjee and Devisha Sasidevan -- Chapter 7. Researching Adolescents and Youth in India: An Assessment of Data Quality and Research Capacity Geeta Sethi and Shalini Bharat.
Keywords: Developmental psychology; Quality of life; Medical policy; Developmental Psychology; Quality of Life Research; Health Policy